Perkembangan Industri Halal Fesyen: Peluang dan Tantangan - Afiyah, Afiyah (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
The growth of the Muslim fashion industry in Indonesia is increasing, halal fashion is not always clothes and headscarves but accessories, shoes and bags. This development raises concerns regarding the raw materials used, the production process, storage, distribution, marketing, and consumers who cannot be combined with haram objects. This research aims to examine the development, opportunities and challenges of the halal fashion industry in Indonesia using literature study methods originating from scientific journals, books, literature and supporting websites. The result is a developed community lifestyle that still pays attention to sharia rules in dressing, and there is a large opportunity for e-commerce users, millennials and Gen Z, who will add to the halal fashion trend. However, the challenges are that there are still many competing countries, there is no international standard halal certification, there are many western brand clothes, weak access to exports, technology is still low, and raw materials still come from foreign countries.